Cobalt‐Catalyzed Aqueous Dehydrogenation of Formic Acid. Issue 36 (10th May 2019) - Zhou, Wei; Wei, Zhihong; Spannenberg, Anke; Jiao, Haijun; Junge, Kathrin; Junge, Henrik; Beller, Matthias
Abstract: Among the known liquid organic hydrogen carriers, formic acid attracts increasing interest in the context of safe and reversible storage of hydrogen. Here, the first molecularly defined cobalt pincer complex is disclosed for the dehydrogenation of formic acid in aqueous medium under mild conditions. Crucial for catalytic activity is the use of the specific complex 3 . Compared to related ruthenium and manganese complexes 7 and 8, this optimal cobalt complex showed improved performance. DFT computations support an innocent non‐classical bifunctional outer‐sphere mechanism on the triplet state potential energy surface. Abstract : Co catalysis : The first molecularly defined cobalt pincer complex is disclosed for the dehydrogenation of formic acid in aqueous medium under mild conditions. Crucial to success is the use of a PNP pincer dentate Co I complex.